(3JHjjV GdGehGd h SQjI GYeGd GdeUGQa (B:s (3BdjGJ ecGaMI h eYGdLI GdGehGd (B/s ((3GdbGgQI(B: s (3efThQGJ GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2007)
(3JHjjV GdGehGd hSQjI GYeGd GdeUGQa(B: (3BdjGJ ecGaMI heYGdLI ZSd GdGehGd (B: (3HMhK hGhQGb Yed edJbi (B"(3ZSd GdGehGd(B"(3, GdefYbO aj GdTGQbI HOhdI GdGeGQGJ GdYQHjI GdeJMOI aj aHQGjQ (B2007 [(3h(B] (3fOhI (B"(3JHjjV GdGehGd hSQjI GYeGd GdeUGQa(B" (3GdefYbO aj GdbGgQI HLeghQjI eUQ GdYQHjI aj GHQjd (B2007 (3hGdeMGhQ cGdJGdj (B: (3fOhI JHjV GdCehGd hSQjI CYeGd GdeUGQa , hQTI Yed CdjGJ ecGaMI JHjV GdCehGd , edJbi ZSd GdCehGd hCdjGJ ecGaMI heYGdLI ZSd GdCehGds
Keywords: (3GdHfhc ,LQGFe GdHfhcs; (3JHjjV GehGds